2023
DOI: 10.1038/s41598-023-29007-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of combined transbronchial lung cryobiopsy and conventional forceps biopsy for lung malignancies: a prospective cohort study

Abstract: There are few prospective reports of transbronchial lung cryobiopsy (TBLC) for malignant tumors in combination with forceps biopsy. We investigated the clinical parameters in which TBLC is superior to forceps biopsy. This is a prospective cohort study to analyse the efficacy of TBLC for suspected malignancy. TBLC was performed after brushing cytology and forceps biopsy, and the diagnostic yield for TBLC, brushing cytology, and forceps biopsy were examined. Adverse events were defined as those requiring additio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
6
2
Order By: Relevance
“…13 A recent study by Kinoshita et al reported a 100% success rate of NGS with TBC (n = 26). 25 Compared to the histological comparator of a 1.9 mm-diameter cryoprobe, the diagnostic yield of NGS testing in this study was not significantly different. In addition, the 1.1 mm-diameter cryoprobe is easy to insert into more peripheral regions and flexible enough to introduce where the bronchial bending angle is steep, such as the apical segment of the upper lobes.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…13 A recent study by Kinoshita et al reported a 100% success rate of NGS with TBC (n = 26). 25 Compared to the histological comparator of a 1.9 mm-diameter cryoprobe, the diagnostic yield of NGS testing in this study was not significantly different. In addition, the 1.1 mm-diameter cryoprobe is easy to insert into more peripheral regions and flexible enough to introduce where the bronchial bending angle is steep, such as the apical segment of the upper lobes.…”
Section: Discussioncontrasting
confidence: 54%
“…Udagawa et al reported 90% and 75% success rates for whole exome and RNA sequencing, respectively ( n = 18) 13 . A recent study by Kinoshita et al reported a 100% success rate of NGS with TBC ( n = 26) 25 . Compared to the histological comparator of a 1.9 mm‐diameter cryoprobe, the diagnostic yield of NGS testing in this study was not significantly different.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Recent studies have reported that cryobiopsy is practical, efficient, and reasonably safe for diagnosing PPLs [5][6][7] . Furthermore, cryobiopsy increases the diagnostic yield of ground-glass lesion 8) .…”
Section: Discussionmentioning
confidence: 99%